Dive into UDL : Immersive Practices to Develop Expert Learners - Grant, Kendra; Perez, Luis, 1972- (Book collections on Project MUSE., 2018)
"Universal Design for Learning (UDL) is a framework for designing instruction that meets the needs of every learner. This book provides an overview of UDL, showing how to offer flexibility in methods of presentation, student participation and expression to support high achievement for all students, including those with disabilities or limited English proficiency. Dive into UDL shows K-12 educators how to incorporate UDL in their instructional design and engage in continuous professional growth. The book will also appeal to those in coaching positions and to administrators seeking to support their staff"--Provided by publisher.